Bacteria-derived chimeric toxins as potential anticancer agents - Khoshnood, Saeed; Fathizadeh, Hadis; Neamati, Foroogh; Negahdari, Babak; Baindara, Piyush; Abdullah, Mohd Azmuddin; Haddadi, Mohammad Hossein (Frontiers in Oncology, 2022)
Cancer is one of the major causes of death globally, requiring everlasting efforts to develop novel, specific, effective, and safe treatment strategies. Despite advances in recent years, chemotherapy, as the primary treatment for cancer, still faces limitations such as the lack of specificity, drug resistance, and treatment failure. Bacterial toxins have great potential to be used as anticancer agents and can boost the effectiveness of cancer chemotherapeutics. Bacterial toxins exert anticancer effects by affecting the cell cycle and apoptotic pathways and regulating tumorigenesis. Chimeric toxins, which are recombinant derivatives of bacterial toxins, have been developed to address the low specificity of their conventional peers. Through their targeting moieties, chimeric toxins can specifically and effectively detect and kill cancer cells. This review takes a comprehensive look at the anticancer properties of bacteria-derived toxins and discusses their potential applications as therapeutic options for integrative cancer treatment.